Short Communication: Ethnobotanical study of wild and cultivated vegetables in the Eastern Cape Province, South Africa - Alfred Maroyi (Society for Indonesian Biodiversity, 2020)
Abstract. Maroyi A. 2020. Short Communication: Ethnobotanical study of wild and cultivated vegetables in the Eastern Cape Province, South Africa. Biodiversitas 21: 3982-3988.  Vegetables are an important component of agricultural biodiversity required for providing a wide range of ecosystem goods and services. The current study was undertaken in the Eastern Cape Province, South Africa to document wild and cultivated vegetables. Research data were collected by means of interviews and field surveys carried out in different seasons with one hundred and thirty-eight randomly selected participants. During the interviews, we documented information on names of edible vegetables, uses, plant parts consumed, and their preparation. A total of 32 species belonging to 26 genera and 15 families were recorded in the study area. The plant families with highest number of vegetable species were Amaranthaceae, Asteraceae, and Solanaceae with at least four species each. The main uses of vegetables identified in the study area were leafy vegetables (59.4%), edible fruits and tubers (21.9% each), culinary herbs or spices (12.5%), edible seeds (9.4%) and edible stems (6.3%). The species which were categorized as important with relative frequency of citation (RFC) values >0.3 were Brassica oleracea, Solanum tuberosum, Cucurbita moschata, Spinacia oleracea, and Cucurbita maxima. Both vegetable species collected from the wild and conventional vegetables cultivated in home gardens are important to livelihoods needs of the local people.